Textural properties of electrospun magnesium oxide (MgO) nanofibers / Hashimah Hashim, Azyan Mohamad Shabari and Puteri Sarah Mohamad Saad - Hashim, Hashimah; Mohamad Shabari, Azyan; Mohamad Saad, Puteri Sarah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2021)
The optimized morphology of electrospun magnesium oxide (MgO) nanofibers (NFs) can be achieved according to the parameters set during the fabrication process. However, not all materials can be synthesized together as it depends on the application needs. This research aims to study the factors that influence the morphology of the MgO NFs due to material preparations and electro spinning parameters. The research is based on data obtained from previous research papers that were analysed using MATLAB R2019a software to evaluate the effect on MgO nanofibers synthesized with different materials. The study was focused on textural properties of nanofibers such as pore-volume and fiber diameter. Based on the analysis obtained, researchers need to consider using polymer material during the electro spinning fabrication. Each type of the polymer used will produce different values of the MgO NFs diameter after calcination process. Poly-propylene glycol polymer showed a very significant difference in the fiber diameter size in the range of 60 to 76 nm as compared to polylactic acid produced big size of fiber diameter in between 3300 to 6900 nm. The analysis showed that the use of nitrogen as a carrier gas in the fabrication of electrospun MgO NFs may produce a good quality of the nanofibers.